Assessment of the nitrogen fertilizer split-application on maize grain yield and profitability on Nitisols of South-Kivu, Eastern D.R. Congo - Patient M. Zamukulu; Espoir M. Bagula; Jean M. Mondo; Géant B. Chuma; Gisèle M. Bulonza; Sarah Mwaluke; Yannick Mugumaarhahama; Céphas B. Mwimangire; Eloïs L. Cinyabuguma; Antoine K. Lubobo; Gustave N. Mushagalusa (CABI Agriculture and Bioscience)
Abstract Soil depletion constitutes a major challenge for agriculture and food security in highlands of eastern Democratic Republic of Congo (DRC). This study aimed to assess the effectiveness of the split-application of nitrogen fertilizer on grain yield and profitability of maize on Nitisols in eastern DRC. The urea fertilizer (100 kg ha−1) was applied in single, two, and three split-applications on three maize varieties for two cropping seasons. Results showed that maize growth and yield parameters varied significantly with N splitting strategy, varieties, and cropping season (p < 0.01). The single N application at the 45th day after sowing presented the highest grain yield (5.5 t ha−1) compared to split-applications for both cropping seasons. The variety 'ZM 627' had the highest grain yield in both seasons (5.4 and 5.8 t ha−1 for 2017 and 2018 cropping seasons, respectively). The benefit–cost ratio analysis showed that single application was more profitable, i.e. 1.63 USD kg−1 of fertilizer compared to two (0.6 USD kg−1) and three splits (0.22 USD kg−1 of fertilizer), though dependent on used varieties. The trend was the same for agronomic efficiency (AE); the single application yielded 11 kg kg−1 of maize grains. In addition, the split applications resulted in additional labor costs. Results from this study do not, therefore, recommend the N splitting strategy for maize on South-Kivu Nitisols.